2013
DOI: 10.4314/wsa.v39i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical and geochemical characteristics of thermal springs and algal diversity in Limpopo Province, South Africa

Abstract: Algal species commonly occur in thermophilic environments and appear to have very wide geographical distributions. Presence of algal species is strongly influenced by temperature, pH and mineral content of thermal waters. No research has previously been documented on the algal diversity in South African thermal springs. This paper describes the algal distribution in 6 thermal springs in Limpopo Province, South Africa, and attempts to link this to the physical and geochemical properties of the springs. Water sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…There are over 90 thermal springs identified within South Africa (Olivier et al, 2011 ) and, since volcanic activity has not occurred in over 90 million years, these thermal springs have been attributed to the deep circulation of groundwater (Olivier et al, 2008 ). The bacterial and algal diversity of the springs have been reported by Tekere et al ( 2011 , 2012 ) and Jonker et al ( 2013 ) along with geochemical data (Olivier et al, 2008 ). Additionally, South Africa is home to 1600 mines and 8 of the 10 deepest mines in the world (Kidd Creek Mine and Creighton Mine of Canada are the other two).…”
Section: Introductionmentioning
confidence: 74%
“…There are over 90 thermal springs identified within South Africa (Olivier et al, 2011 ) and, since volcanic activity has not occurred in over 90 million years, these thermal springs have been attributed to the deep circulation of groundwater (Olivier et al, 2008 ). The bacterial and algal diversity of the springs have been reported by Tekere et al ( 2011 , 2012 ) and Jonker et al ( 2013 ) along with geochemical data (Olivier et al, 2008 ). Additionally, South Africa is home to 1600 mines and 8 of the 10 deepest mines in the world (Kidd Creek Mine and Creighton Mine of Canada are the other two).…”
Section: Introductionmentioning
confidence: 74%
“…Both Caudovirales genomes did not have a confirmed host, but the presence of green microbial mat-patches around the contours of the hot spring, implied that filamentous Cyanobacteria and unclassified Gemmata species were the potential hosts, respectively. The last, based on the proximity of some viral predicted proteins with bacteria from well characterized microbial mats present in a nearby hot spring ( Tekere et al, 2011 ; Jonker et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stockner (1967) found Mougeotia sp. in 47ºC thermal streams of Mount Rainier, Sakai et al (1995) reported that the temperature of the hot spring where they collected their Chlorella strain ranged between 20-70ºC, and Jonker et al (2013) found Chlorella in > 60ºC thermal water sources in Limpopo province, South Africa. In our research, a Chlorellaceae strain was found in water as hot as 52.4ºC at the Tiberias hot springs.…”
Section: Discussionmentioning
confidence: 99%
“…The main genera comprising the Chlorellaceae family are Chlorella, Micractinium, Parachlorella, Dictyosphaerium and Auxenochlorella (Guiry & Guiry, 2015). These members can be found in a variety of habitats including fresh and brackish waters, hot springs and even rock surfaces in Antarctica, at temperatures ranging overall between freezing to 70ºC (Sakai et al, 1995;Hu et al, 2008;Jonker et al, 2013;Onay et al, 2014). Chlorella species in particular are used as animal feed, food supplements and nutraceuticals (e.g.…”
Section: Introductionmentioning
confidence: 99%